The impact of sedation and analgesia scores on prognosis in critically ill sepsis patients with sepsis-associated encephalopathy: a retrospective analysis - Wei, Weiqin; Fang, Donghai; Hu, Xiaochun; Zhou, Yongfang; Fu, Jiangquan; Wu, Guofeng (Frontiers in Neurology, 2025)
BackgroundSepsis is a critical condition resulting from a poor immune response to infection, often leading to complications like sepsis-associated encephalopathy (SAE). Research suggests a link between sedation and analgesia use and SAE development in intensive care unit (ICU) patients, but study inconsistencies limit definitive conclusions. This study aims to explore the relationship between sedation and analgesia scores and the occurrence of SAE in the ICU, as well as their impact on clinical effectiveness and patient prognosis.MethodsBetween January 1, 2021, and August 30, 2022, a retrospective analysis of 356 sepsis cases was conducted in the Emergency ICU of the Affiliated Hospital of Guizhou Medical University. After excluding 102 patients, 219 were included and divided into SAE and non-SAE groups for analysis.ResultsThe SAE group demonstrated higher age, Sequential Organ Failure Assessment (SOFA) scores, and APACHE II scores, alongside longer ICU durations and lower Glasgow Coma Scale (GCS) scores (p < 0.05) compared to the non-SAE group. Furthermore, the levels of lactate dehydrogenase (LDH), interleukin-6 (IL-6), and blood lactate were significantly increased in the SAE group (p < 0.05). After adjustments for baseline characteristics, biochemical indices, risk assessment scores, and clinical features, multivariate analysis identified age, APACHE II score, LDH, IL-6, oxygenation index, base excess (BE), and base excess of extracellular fluid (BE(ecf)) as significant risk factors for encephalopathy in septic patients (p < 0.05). ROC curve analysis indicated that the area under the curve (AUC) for predicting SAE was 0.810 (95% CI: 0.785–0.831) for the APACHE II score, 0.780 (95% CI: 0.743–0.801) for IL-6, and 0.769 (95% CI: 0.730–0.836) for BE. Sensitivity values were 81.1, 77.4, and 70.6%, while specificity values were 70.3, 72.3, and 71.3%. Patients with sepsis influenced by these factors exhibited an increased likelihood of developing SAE. Additionally, RASS and BPS scores were significantly correlated with the prognosis of sepsis patients (p < 0.05).ConclusionThe study demonstrated that patients with SAE exhibit physiological disturbances, including elevated inflammatory markers (IL-6 and LDH), impaired oxygenation, and acid–base imbalances, which may contribute to more severe clinical courses. Additionally, RASS and BPS scores were found to be reliable indicators of patient prognosis in sepsis. These findings may guide clinical practice in managing patients with SAE.